2013
DOI: 10.1002/lary.24006
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene‐covered nitinol stent graft for treatment of carotid artery blowout syndrome in head and neck cancer patients

Abstract: Covered stent placement is highly feasible and proved effective without major complications in CBS due to carotid axis bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…The MINORS quality scores ranged from 7 to 11. An overview of the characteristics of the studies is provided in Table …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MINORS quality scores ranged from 7 to 11. An overview of the characteristics of the studies is provided in Table …”
Section: Resultsmentioning
confidence: 99%
“…An overview of the characteristics of the studies is provided in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Of the 292 patients, 26 patients did not have relevant or extractable data. Of the remaining 266 patients, 137 were treated with embolization (77 for ICA and/or CCA and 60 for ECA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The indications for RE of group 2B patients were the patients at risk of permanent carotid occlusion, such as those with contralateral carotid occlusion, intolerance to a balloon occlusion test, or emergency status of the patient precluding an occlusion test [ 13 , 14 ]. The technique of RE has been described in previous studies [ 14 , 16 ]. We used a self-expandable stent-graft, including Wallgraft stent-graft (Boston Scientific Corp, Natick, Mass), Fluency stent-graft (Bard/Angiomed GmbH & Co, Karlsruhe, Germany), or Viabahn (W.L.…”
Section: Methodsmentioning
confidence: 99%
“…Various endovascular treatment algorithms have been proposed but none have been standardized [ 13 , 15 ]. Although a reconstructive method with stent-graft has been reported to be a temporary method of management, recent reported series have shown that this method can yield promising results [ 14 , 16 18 ]. Clinical severity has been reported to influence the rebleeding rate of patients with PCBS, but this has not widely validated [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,[16][17][18] The rates of stent-related complications, such as instent thrombosis, cerebral ischemia, and septic embolism, have been reported to approach 25%-50%, with neurologic complication rates of 10%-27.8%. 9,29 The unacceptably high poststenting complication rates could be attributable to inadequate antiplatelet therapy during clinical emergencies and contamination from the exposed artery. Therefore, we did not consider that routine stent-graft deployment was justified in patients with CBS, though it might be beneficial if both the initial CTA and confirmative BTO were considered risky for borderzone infarction.…”
Section: Discussionmentioning
confidence: 99%